Injury and spatial distribution of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) in Onion Allium cepa (Alliaceae) in Alto Paranaíba, Minas Gerais, Brazil - Fernandes, Flávio L.; Diniz, Juno F. S.; Alves, Flávia M.; Silva, Luiz O. D. (Entomological News, 2012)
Genetically modified plants protect the crop of maize (Zea mays) from fall armyworms (Spodoptera frugiperda) (J. E. Smith), which are responsible for great losses in maize crops. This plague might spread to other areas and feed on alternative hosts. Among these hosts, attack of such caterpillars on commercial crops of onions (Allium cepa) has been noted in Alto do Paranaíba, Minas Gerais, Brazil. This paper reports, for the first time, the damage, the percentage of attack, and a possible migration of S. frugiperda from genetically modified maize to onion crops. The caterpillars penetrate the tube sheet and cut the onion leaf tissue in the apical-basal direction, causing the weakening of the sheet, which ends up breaking with the wind. It was found that the attack of the caterpillars in onion crops began in the region close to the genetically modified maize crops. That probably happened due to the repellency of the adult S. frugiperda from such genetically modified crops.
Keywords: Fall armyworm; Maize; Geostatistics; Spatial dynamics